Digital Transformation in Management Accounting: Towards Efficiency and Competitive Advantage - Rosmala, Cici (LPPM Universitas Terbuka, 2024)
Exploring the impact of digital transformation on management accounting, this study aims to identify pathways towards enhanced efficiency and competitive advantage. Employing a qualitative research design, the investigation involved a purposive sampling of medium-sized enterprises, with data gathered through structured interviews and analyzed using thematic analysis. The findings reveal significant shifts in operational dynamics, notably in data management and strategic decision-making, with themes highlighting the integration of advanced technologies fostering streamlined processes. Discussion centers on the implications of these transformations for organizational agility and market positioning. The study concludes with recommendations for leveraging digital tools to reinforce management accounting practices, ultimately contributing to sustained organizational growth